Study of vibration in hydraulic power assisted steering system [electronic resource] - 424793 Hamaznoor Nizam Hassan Basri (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007